Characterizing EPR-mediated passive drug targeting using contrast-enhanced functional ultrasound imaging - Theek, Benjamin; Gremse, Felix; Kunjachan, Sijumon; Fokong, Stanley; Pola, Robert; Pechar, Michal; Deckers, Roel; Storm, Gert; Ehling, Josef; Kiessling, Fabian; Lammers, Twan (Journal of controlled release, 2014)
The Enhanced Permeability and Retention (EPR) effect is extensively used in drug delivery research. Taking into account that EPR is a highly variable phenomenon, we have here set out to evaluate if contrast-enhanced functional ultrasound (ceUS) imaging can be employed to characterize EPR-mediated passive drug targeting to tumors. Using standard fluorescence molecular tomography (FMT) and two different protocols for hybrid computed tomography-fluorescence molecular tomography (CT-FMT), the tumor accumulation of a ~10 nm-sized near-infrared-fluorophore-labeled polymeric drug carrier (pHPMA-Dy750) was evaluated in CT26 tumor-bearing mice. In the same set of animals, two different ceUS techniques (2D MIOT and 3D B-mode imaging) were employed to assess tumor vascularization. Subsequently, the degree of tumor vascularization was correlated with the degree of EPR-mediated drug targeting. Depending on the optical imaging protocol used, the tumor accumulation of the polymeric drug carrier ranged from 5 to 12% of the injected dose. The degree of tumor vascularization, determined using ceUS, varied from 4 to 11%. For both hybrid CT-FMT protocols, a good correlation between the degree of tumor vascularization and the degree of tumor accumulation was observed, within the case of reconstructed CT-FMT, correlation coefficients of ~0.8 and p-values of <0.02. These findings indicate that ceUS can be used to characterize and predict EPR, and potentially also to pre-select patients likely to respond to passively tumor-targeted nanomedicine treatments.
Keywords: Cancer; kontrastní látky; EPR; myši nahé; permeabilita; Contrast Media; mikrobubliny; Permeability; Nanomedicine; krevní objem; Ultrasonography; Mice, Nude; Drug Delivery Systems; Theranostics; zvířata; Microbubbles; Acrylamides; akrylamidy; Enbucrilate; enbukrylát; ultrasonografie; regionální krevní průtok; lékové transportní systémy; Neoplasms; Drug targeting; nádorové buněčné linie; nádory; Tomography; Animals; Cell Line, Tumor; Regional Blood Flow; HPMA; Blood Volume; tomografie